2018
DOI: 10.1123/jab.2017-0256
|View full text |Cite
|
Sign up to set email alerts
|

Laboratory Evaluation of Low-Cost Wearable Sensors for Measuring Head Impacts in Sports

Abstract: Advances in low-cost wearable head impact sensor technology provide potential benefits regarding sports safety for both consumers and researchers. However, previous laboratory evaluations are not directly comparable and do not incorporate test conditions representative of unhelmeted impacts. This study addresses those limitations. The xPatch by X2 Biosystems and the SIM-G by Triax Technologies were placed on a National Operating Committee on Standards for Athletic Equipment (NOCSAE) headform with a Hybrid III … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
38
2

Year Published

2019
2019
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 51 publications
(41 citation statements)
references
References 41 publications
1
38
2
Order By: Relevance
“…This finding is consistent with previous evaluations of the SIM-G and other inertial head impact sensors. 15,21,24 Limitations common to inertial sensor technology may contribute to SIM-G inaccuracies reported here. For example, the SIM-G underreported values of PLA and PRV in both headgears, a pattern that is consistent with the insufficiently low sampling rates (41 kHz) used by many head impact sensors.…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations
“…This finding is consistent with previous evaluations of the SIM-G and other inertial head impact sensors. 15,21,24 Limitations common to inertial sensor technology may contribute to SIM-G inaccuracies reported here. For example, the SIM-G underreported values of PLA and PRV in both headgears, a pattern that is consistent with the insufficiently low sampling rates (41 kHz) used by many head impact sensors.…”
Section: Discussionmentioning
confidence: 96%
“…Separate linear regressions were computed to quantify the peak kinematic value registered by the SIM-G as a function of reference values from the headform in each headgear. The tolerance for practical equivalence between the SIM-G and reference peak values was set to 0.2, a liberal threshold recommended by a previous evaluation of the SIM-G. 21 SIM-G kinematic values were considered practically equivalent if the 95% CI of the regression slope (B) for the interaction term remained between 0.8 and 1.2. In other words, this analysis sought to determine whether there was a 95% probability that the SIM-G would record a value within 20% of the reference kinematic value.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The SIM-G validation data are inconsistent, with investigations reporting optimal impact detection (100% of non-helmeted impacts detected and 80% of helmeted impacts detected in one study, 21 99% of helmeted impacts detected in another study 22 ) and linear acceleration validity (no difference between headform and SIM-G linear acceleration at low and medium energy impacts in one study, 23 approximately 14.25% error on average in another study 22 ) while a separate investigation reported less than optimal acceleration validity (underpredicted linear and rotational acceleration in helmeted and non-helmeted condition). 24 No on-field head impact biomechanics data collection system is perfect. The SIM-G was chosen for this study because it has the ability to record head impact data from both helmeted and non-helmeted participants.…”
Section: Twentymentioning
confidence: 99%